THE IMPACT OF GLOBAL CRISES ON FINANCIAL MARKETS - Fayziyev Samandar Sobir ugli (Innovation Science and Technology, 2025)
Global financial markets are highly susceptible to the disruptive effects of global crises, including economic recessions, pandemics, and geopolitical conflicts. This article analyzes the impact of major crises specifically the 2008 Global Financial Crisis, the COVID-19 pandemic, and the 2022 Russia–Ukraine conflict on financial markets. By integrating empirical data, we examine market volatility, investor behavior, and government interventions during these crises. Historical evidence suggests that financial markets react with sharp declines in stock indices, increased demand for safe-haven assets, and liquidity contractions. Future financial market stability will depend on adaptive monetary policies, international cooperation, and the resilience of financial institutions to mitigate systemic risks.